2017
DOI: 10.3390/nu9050477
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Effects of Phenolic Acids: Molecular Mechanism of Action

Abstract: The neuroprotective role of phenolic acids from food has previously been reported by many authors. In this review, the role of phenolic acids in ameliorating depression, ischemia/reperfusion injury, neuroinflammation, apoptosis, glutamate-induced toxicity, epilepsy, imbalance after traumatic brain injury, hyperinsulinemia-induced memory impairment, hearing and vision disturbances, Parkinson’s disease, Huntington’s disease, anti-amyotrophic lateral sclerosis, Chagas disease and other less distributed diseases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
99
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(102 citation statements)
references
References 117 publications
(93 reference statements)
1
99
0
2
Order By: Relevance
“…Polyphenols are organic metabolites present in plants (Cory et al, 2018) and widely distributed in a variety of dietary sources (Aherne and O'Brien, 2002;Kim et al, 2009): fruits, vegetables, legumes, whole grains, seeds, nuts, extra virgin olive oil, red wine, coffee, tea, chocolate, herbs and spices (Rusconi and Conti, 2010;Fu et al, 2011;Regueiro et al, 2014;Vallverdú-Queralt et al, 2014, 2015Talhaoui et al, 2016). Despite their zero energy contribution (Ruiz et al, 2009) they act as bioactive dietary components associated with multiple positive health effects (An-Na et al, 2014;Ganesan and Xu, 2017;Szwajgier et al, 2017;Renaud and Martinoli, 2019) due to their regulating action on metabolism, chronic diseases and cell proliferation (Tressera-Rimbau et al, 2017). Polyphenols have a chemical structure with properties that make them the compounds with the greatest antioxidant action: o-diphenolic group, 2-3 double bond conjugated with the 4-oxo function and hydroxyl groups (OH) in positions 3 and 5 (Ruiz et al, 2009).…”
Section: Pterostilbene and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Polyphenols are organic metabolites present in plants (Cory et al, 2018) and widely distributed in a variety of dietary sources (Aherne and O'Brien, 2002;Kim et al, 2009): fruits, vegetables, legumes, whole grains, seeds, nuts, extra virgin olive oil, red wine, coffee, tea, chocolate, herbs and spices (Rusconi and Conti, 2010;Fu et al, 2011;Regueiro et al, 2014;Vallverdú-Queralt et al, 2014, 2015Talhaoui et al, 2016). Despite their zero energy contribution (Ruiz et al, 2009) they act as bioactive dietary components associated with multiple positive health effects (An-Na et al, 2014;Ganesan and Xu, 2017;Szwajgier et al, 2017;Renaud and Martinoli, 2019) due to their regulating action on metabolism, chronic diseases and cell proliferation (Tressera-Rimbau et al, 2017). Polyphenols have a chemical structure with properties that make them the compounds with the greatest antioxidant action: o-diphenolic group, 2-3 double bond conjugated with the 4-oxo function and hydroxyl groups (OH) in positions 3 and 5 (Ruiz et al, 2009).…”
Section: Pterostilbene and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Based on increasing evidence of the contributions of neuronal pro-inflammatory mediators and oxidative stress in the pathogenesis and development of depression, new therapeutic tools have been experimentally tested in order to improve the current treatment of depressive disorders. In this context, hydroxylated and/or methoxylated aromatic acids have shown promising results as neuroprotective agents [25]. Among these acids, there are phenolic acids, which are divided into hydroxybenzoic acids and hydroxycinnamic acids, based on C 6 -C 1 and C 6 -C 3 skeletons, respectively [26].…”
Section: Antidepressant Activity Of Cinnamic Acidsmentioning
confidence: 99%
“…This finding is in accordance with a previous study performed by Oglodek (2017), in which it was identified that major depressive disorders, associated Reports of antidepressant activity on these compounds indicate that they may be an alternative treatment option for depression [17]. Cinnamic acids are a group of aromatic carboxylic acids with carbonic skeleton C6-C3 ( Figure 2) found in a variety of plants and foods, for which the biosynthetic route can generate several secondary metabolites such as coumarins, lignans, isoflavonoids, flavonoids, and others natural products [18].Cinnamic acids and their derivatives have attracted the attention of researchers due to their wide distribution in nature, low toxicity, structural diversity, and pharmacological actions [19], as anti-inflammatory [20], antioxidant [21], antitumor [22], hypoglycemic [23], antidepressant [24], and cytoprotective actions of neuroinflammation in neurodegenerative diseases [25]. Considering the importance of cinnamic acids as bioactive substances and their presence in various foods and medicinal plants, this review discusses the antidepressant action mechanisms of these compounds, demonstrating their therapeutic potential for depressive disorders.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in many fields such as medicine, ZnO nanoparticles have been used for its photocatalytic and antimicrobial properties. Zinc oxide nanoparticles can be used as photocatalytic pigments, chemical sensors, drug carriers in targeted drug delivery, and the provision of cosmetics such as sunscreens [11].It is important to produce zinc oxide nanoparticles that utilize cost-effective methods to produce uniform nanoparticles [12,13]. On the other hand, one of the problems that threaten the environment and human health is the use of hazardous materials and reagents in preparing various materials including nanomaterials.…”
mentioning
confidence: 99%
“…It is important to produce zinc oxide nanoparticles that utilize cost-effective methods to produce uniform nanoparticles [12,13]. On the other hand, one of the problems that threaten the environment and human health is the use of hazardous materials and reagents in preparing various materials including nanomaterials.…”
mentioning
confidence: 99%